Retratos foucaultianos da deficiência e da ingovernabilidade na escola do governo das diferenças a outro paradigma de inclusão - Pagni, Pedro Angelo (Editora Oficina Universitária, 2023)
The book "Foucauldian portraits of disability and ungovernability at school: from the government of differences to another paradigm of inclusion" problematizes the scientific paradigm on which the perspectives of inclusive education and its state policies in Brazil are based, with a view to indicating others paths in the light of the philosophies of difference. By discussing the limits and possibilities of Foucault's thought to portray the theme, it elaborates an interlocution with contemporary French and Italian intellectuals of this philosopher, specifically, to address this educational theme. It invites reflection, in this way, the reader willing to think about this other paradigm of inclusion - less scientific, more aesthetic-political, produced by the cartography of the encounter with the heterotopic bodies of the disability and its ungovernability propitiated by its presence in the school.